PENGARUH BI RATE, INFLASI DAN IHSG TERHADAP HASIL INVESTASI SAHAM Studi Kasus pada Hasil Investasi Saham PT TASPEN (PERSERO) Tahun 2010-2015 - FX Rudolf Sitanggang; Wahyu Hidayat (Universitas Diponegoro, 2016)
The capital market is a market where long-term financial instrument traded. Capital market have an important role for the economy of a country because of the stock market can be a means for companies to raise funds from the public (investors) to be used for business development by investing in the financial sector such as stocks and bonds. Shares investment result are influenced by many factors, one of which is the macroeconomic factors. In conjunction with the Indonesian macro-economy, the bank acts as a control over the monetary policies issued by Bank Indonesia. Because of this, this study raised the BI Rate, Inflation and ICI as macroeconomic factors that allegedly affect the investment of result shares.This study aims to determinate effect of BI Rate, Inflation and ICI against the Result of Stock Investment in years 2010-2015. Methods of data collections using secondary data. Scale measurements using a measuring scale ratio. In linear regression analysis was used ang the significance test using SPSS versi 15.0From the analysis of data it can be concluded that BI rate has no significant effect on Result of Investment Stock. Inflation does not have a significant effect of Result of Investment Stock. ICI has no significant effect on Result of Investment Stock. Simultaneously, BI Rate, Inflation and ICI has no significant effect on Result of Investment Stock.The advice can be give that PT Taspen (Persero) can be also consider other factors in addition to the factors BI Rate, Inflation, and ICI as a material consideration in decision making to doing invest stock.